Experimental dissolution of biopolymer-coated phosphorus fertilizers applied to a soil surface: Impact on soil pH and P dynamics - Saloua Fertahi; Chiara Pistocchi; Gabrielle Daudin; M'barek Amjoud; Abdallah Oukarroum; Youssef Zeroual; Abdellatif Barakat; Isabelle Bertrand (Annals of Agricultural Sciences, 2022)
Biopolymer-coated phosphorus fertilizers have shown promising results in slowing the release of P. However, their dissolution behaviour has been studied mainly in water, and their impacts on soil properties have rarely been addressed. The aim of this study was to compare the dissolution of P from uncoated triple superphosphate (TSP) and biopolymer-coated TSP fertilizers at the surface of cropped Mediterranean soils and to evaluate their impacts on the soil pH and the distributions of several P pools. The experimental treatments were: no fertilizer, uncoated TSP, TSP coated with lignin and TSP coated with lignin and carrageenan. The spatial and temporal variations in the pH of the fertilized soils were investigated using optodes. The concentrations of different pools of P (available P, microbial P), and total P as well as P recovery at different distances from the granules were determined. The coated TSP acidified the soil to a radius of 14 mm around each fertilizer granule, while the acidification spread to 21 mm in the treatment with the uncoated TSP. Moreover, an increase in microbial P was observed in the soil treated with coated TSP, possibly due to the carbon input and the consequent increase in microbial biomass. However, slower P-release was observed from the coated TSP due to the effect of the coating barrier. The P recovery results showed P migration within a 21 mm radius from each granule, and the P recovery from the TSP coated with lignin alone was significantly greater than that from the uncoated TSP treatment.